2018
DOI: 10.1302/0301-620x.100b2.bjj-2017-0895.r1
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic revision total hip arthroplasty in the elderly

Abstract: Even after controlling for patient and procedural characteristics, aseptic revision THA is associated with greater risks in patients aged ≥ 80 years compared with younger patients. This is important for counselling and highlights the need for medical optimization in these vulnerable patients. Cite this article: 2018;100-B:143-51.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…Previous authors have demonstrated that advanced patient age is associated with higher risks of perioperative complications and an extended length of stay, particularly in octogenarians. 24,25 Interestingly, in the present study our model predicts a shorter length of stay as age increases. This is counterintuitive, as one would expect older patients to have an increased incidence of comorbidities and complications, thereby necessitating a longer LOS in the hospital.…”
Section: Discussionsupporting
confidence: 45%
“…Previous authors have demonstrated that advanced patient age is associated with higher risks of perioperative complications and an extended length of stay, particularly in octogenarians. 24,25 Interestingly, in the present study our model predicts a shorter length of stay as age increases. This is counterintuitive, as one would expect older patients to have an increased incidence of comorbidities and complications, thereby necessitating a longer LOS in the hospital.…”
Section: Discussionsupporting
confidence: 45%
“…That said, this is a commonly used database in the field, as can be seen by the many recent studies cited. 12345,18192021222324 Second, it is possible that the observations made here may not apply to other NSQIP study populations. That said, the overall conclusions made here mirror those of the previously referenced lumbar study.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, in the last year alone, nine studies have been published on total hip arthroplasty (THA) using NSQIP data. 123456789…”
mentioning
confidence: 99%
“…ASA ratings correlate with patient medical comorbidities and can be helpful in predicting perioperative risks and outcomes. Previous studies have looked at outcomes for nonagenarians and octogenarians in revision procedures [12][13][14][15][16][17]. Bovonratwet et al found revision TKA to be safe in patients aged over 80 years and concluded that octogenarian patients need not be discouraged from revision TKA solely based on their advanced age [14].…”
Section: Discussionmentioning
confidence: 99%
“…Parvizi et al showed that an rTHA can provide substantial clinical benefit to patients over eighty years of age [16]. However, there is additional evidence that an aseptic rTHA may be associated with greater risks in patients 80 years or older compared to younger patients [17].…”
Section: Discussionmentioning
confidence: 99%